Ecological Knowledge, Leadership, and the Evolution of Menopause in Killer Whales. Issue 11 (November 2015) - Brent, Lauren J. N.; Franks, Daniel W.; Foster, Emma A.; Balcomb, Kenneth C.; Cant, Michael A.; Croft, Darren P.
Abstract : ABSTRACT: Nearly all animal species die around the same time they stop reproducing. Only 3 species—humans, killer whales ( Orcinus orca ), and short-finned pilot whales ( Globicephala macrorhynchus )—routinely live 30 years after giving birth to their last baby. Female resident killer whales generally breed between the ages of 12 and 40 years and can survive into their 90s. Accumulating evidence suggests that menopause evolved in both postreproductive humans and killer whales through inclusive fitness benefits gained by helping kin. It is believed that reproductive success and/or survival of relatives is enhanced by long-term survival of females after menopause. It has been hypothesized that postmenopausal females buffer their kin against environmental hardships by storing and providing ecological information. Shortage of salmon is a major contributing factor to mortality and reproductive success in resident killer whales. During the 9-summer salmon migrations, the research team studied leadership in Southern resident killer whales in the North Pacific ocean off the coasts of British Columbia and Washington. More than 700 hours of video footage of 102 individual migrating Southern resident killer whales (58 females and 44 males) was collected and examined. Key findings were as follows: (1) postreproductively aged females were more likely to lead groups during collective movement in salmon foraging grounds and were especially likely to lead in years when salmon were in low supply and more difficult to locate; (2) females are more likely to lead their sons than their daughters. Sons offer greater potential inclusive fitness benefits most likely because they have higher reproductive potential. Sons mate outside the group, and their offspring do not compete for resources within the matriline. These data provide the first evidence that a major benefit for long-term survival after menopause is that postreproductive females act as repositories of ecological knowledge. The oldest and most experienced individuals are those most likely to know where and when to find food when particularly scarce.